Tourism Development Based on Religious Moderation in the Lake Toba Region Perspective of Communication Persuasion and Social Influence - Rasyid, Abdul; Alfikri, Muhammad; Stepani, Riri (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
Domestic tourist objects which are considered to have attractive potential are visited by many Muslim tourists both from within and outside the country, but in reality these tourist objects pay little attention to the comfort of Muslim tourists. Visiting Lake Toba tourist destinations for Muslim tourists is not only about natural beauty, but also about halal food and comfortable places of worship. Halal tourism continues to be an interesting issue to discuss because it is a vital issue for the life of Muslims. It is very risky for Muslims when a tourist destination does not provide comfort regarding the issue of halal food and the availability of places of worship. This paper reviews the concept of religious moderation tourism which can be interpreted as the availability and fulfillment of the needs of Muslims and tourist destinations such as halal food that is not mixed with unclean food, proper places of worship, and various other facilities that are the needs of Muslims. The approach used in this study is a qualitative approach. Data were obtained by conducting interviews with tourism managers, community leaders, the Head of the Culture and Tourism Office, tourism observers and the community. The concept of moderating religious tourism in the Lake Toba area is already underway, such as hotels serving halal food cooked by Muslim workers, providing prayer rooms. However, what has not been seen is the certainty of food halalness with the existence of a halal certificate issued by the competent authority. The facts obtained in the Lake Toba area did not play much of a role in changing the attitudes and behavior of local residents to become more moderate towards foreign Muslim tourists.